A translanguaging perspective on medium of instruction in the CFL classroom. Issue 5 (28th May 2022) - Zhang, Qi; Osborne, Caitríona; Shao, Lijie; Lin, Mei
ABSTRACT: Although recent years have witnessed increasing interest in learning Chinese as a foreign language (CFL) in China and around the world, there seems to be a paucity of research into the medium of instruction in the CFL classroom. This paper describes a study of the practice of MoI choice in the CFL classroom, situated within the framework of translanguaging. Five focus group interviews and eight classroom observations were conducted across five universities in China. Approximately 43 participants participated in the interview stage of the research, while 149 CFL students across eight CFL classrooms were involved in the observation stage, with six students and four teachers also interviewed after the observations. The findings suggest that translanguaging was commonly used by teachers. However, due to limits on resource availability and to the linguistic complexity of a CFL classroom, these translanguaging practices also posed challenges to the teachers. Interestingly, English was predominantly employed for explanatory and elicitation functions, whereas Chinese was chosen mainly for teaching and instructing purposes. While translanguaging practice was observed in both the beginner CFL class and in the more advanced class, the monolingual approach was still predominantly used and advocated across different levels.